Pengaruh Corporate Social Responsibility dan Intellectual Capital Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Industri Dasar dan Kimia, Industri Barang Konsumsi, dan Aneka Industri yang Terdaftar di Bursa Efek Indonesia Periode 2015– 2017) - Mukhzarudfa; Rega C; Achmad Hizazi (Jurnal Akuntansi & Keuangan Unja, 2020)
This study aims to provide empirical evidence of the effect of Corporate Social Responsibility and Intellectual Capital on the value of companies in basic industries and chemical, consumer goods industry, and miscellaneous industry companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 - 2017. The samples in this study are basic industries and chemical, consumer goods industry, and miscellaneous industry companies listed on the Indonesia Stock Exchange (BEI) for 2018 which publishes annual reports for the period 2015 - 2017. The process of selecting samples in this study uses a purposive sampling method. Analysis of the data used in this study are descriptive statistics, classic assumption tests, and multiple linear regression analysis using SPSS. The research’s results showed that Corporate Social Responsibility, Intellectual Capital, profitability, leverage, and firm size had effect towards firm value.